تقويم جودة الأستاذ الجامعي:تحديد الصفات النموذجية الواجب توافرها في الأستاذ الجامعي حسب أراء و تصورات الطلبة - صدقاوي, كمال (جامعة الوادي - University of Eloued, 2023)
هدفت هذه الدراسة للكشف عن آراء وتصورات الطلبة الجامعيين لأهم الصفات النموذجية (الشخصية، المهنية، العلائقية، المعرفية، الخاصة بالتقويم، الإشراف)، الواجب توافرها في الأستاذ الجامعي، لتزويده بمعلومات عن مدى فاعليته التدريسية. حيث قام الباحث باستخدام المنهج الوصفي، ولتحقيق الهدف من الدراسة قام ببناء مقياس خاص بالخصائص الأساسيـــــة للأستاذ الجامعي يحوي عديد الصفات الواجب توافرها فيه، متكون من89 بندا، موزعة على ستة محاور لإختبار الفرضيات، وفق مقياس ليكرت (05 خيارات متدرجة من عالية جدا إلى منخفضة جدا)، تم تطبيقه في جامعة إبن خلدون بتيارت خلال السنة الجامعية 2019/2020، على عينة مكونة من 404 طالب (ة) ماستر 01 و02، بعد التحقق من ثباته وصدقه.. مستخدما برنامج التحليل الإحصائي لتحليل البيانات واختبار صحة فرضيات الدراسة وقد توصلت الدراسة إلى النتائج التالية : - الصفات التي لها علاقة بالجانب الإنساني، المهني، العلائقي، المعرفي، التقويمي، الإشرافي في شخصية الأستاذ الجامعي حضيت باهتمام جل الطلبة، وقد ترجم في المتوسطات العالية المحصل عليها ( 3- 4.25 ). كما كشفت النتائج عن عدم وجود فروق ذات دلالة إحصائية بين متوسط تقديرات الطلبة تعزى لمتغيري الجنس والمستوى. وانطلاقا من النتائج المتوصل إليها خلص الباحث إلى مجموعة من الاقتراحات. Abstract: This study aimed to reveal the views of university students' perceptions of the most important typical traits (personal, professional, relational, cognitive, evaluation, supervision), which must be available in a university professor, to provide him with information on the extent of his teaching effectiveness. Where the researcher used the descriptive approach, and to achieve the goal of the study, he built a scale for the basic characteristics of a university professor that contains many attributes that must be met in him, consisting of 89 items, An item, distributed over six axes to test hypotheses, according to the Likert scale, which was applied at Ibn Khaldoun University 2019/2020, on a sample of 404 students(e) Master 01 and 02, after verifying its reliability and validity.. where the researcher used the spss , The study reached the following results: - The qualities that have to do with the human aspect, professional, relational, cognitive, evaluative, and supervision in the personality of the university professor received the attention of most of the students, and it was translated into the high averages obtained (3-4.25). The results also revealed that there were no statistically significant differences between the average students' estimates due to the gender and level variables. Based on the findings
مقال
Keywords: الفعالية التدريسية ; الأستاذ الجامعي ; الطالب الجامعي ; التقويم ; الصفات الأساسية; teaching effectiveness ; university professor; university student; evaluation; basic characteristics